2021
DOI: 10.1111/jerd.12737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of argon plasma on repair bond strength using nanofilled and microhybrid composites

Abstract: Objectives To evaluate the effect of atmospheric pressure plasma (PLA), sandblasting (SAN), silanization (SIL) and hydrophobic bonding resin (HBR) on the micro‐shear bond strength (MSBS) of fresh nanofilled (NF) or microhybrid (MH) composites to water‐aged nanofilled composite. Materials and methods NF plates were fabricated and stored in distilled water for 4 months. The aged plates were assigned to the groups (n = 6): 1‐ untreated; 2‐ SAN + SIL + HBR; 3‐ HBR; 4‐ PLA + HBR; 5‐ SAN + HBR; 6‐ SAN + PLA + HBR; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The sample sizes varied between 5 [43] to 61[30] in each study. The aging methods included liquid storage (water [3, 9, 27, 44, 45] and saliva [46]), thermocycling [20, 22-25, 29, 31, 32, 42, 47], or a combination of the two [21, 26, 28, 30, 43, 48]. Seven studies [22-25, 30, 43, 46] provided micro-tensile bond strength, four [3, 9, 44, 47] indicated micro-shear bond strength, ten [20, 21, 26-29, 31, 32, 42, 48] gave shear bond strength, and only one [45] evaluated tensile bond strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample sizes varied between 5 [43] to 61[30] in each study. The aging methods included liquid storage (water [3, 9, 27, 44, 45] and saliva [46]), thermocycling [20, 22-25, 29, 31, 32, 42, 47], or a combination of the two [21, 26, 28, 30, 43, 48]. Seven studies [22-25, 30, 43, 46] provided micro-tensile bond strength, four [3, 9, 44, 47] indicated micro-shear bond strength, ten [20, 21, 26-29, 31, 32, 42, 48] gave shear bond strength, and only one [45] evaluated tensile bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…Composite resin restorations must be repaired or replaced, over different time periods following placement due to secondary caries, cracks, marginal discoloration, gaps, cosmetic improvements, shape corrections, and proximal contact closures [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resin composite restorations must be repaired or replaced, over different time periods following placement due to secondary caries, cracks, marginal discoloration, gaps, cosmetic improvements, shape corrections, and proximal contact closures [1][2][3]. Based on the extent of the damage and the seriousness of the defect, repair may be a viable option to replacement.…”
Section: Introductionmentioning
confidence: 99%
“…The surface treatment protocols performed on old resin composites also play a significant role in determining the durability of the repair bond. In vitro research findings had also utilized a variety of surface treatment methods, such as roughening with abrasive papers [20][21][22][23], diamond burs [24][25][26], Al 2 O 3 particles [3,22,27], silica-coated particles [28][29][30], and lasers [31,32] as mechanical, and numerous bonding mechanisms, adhesives, and silanization as chemical surface treatments [3,22,23,27], solely or in combination to overcome the bonding obstacles. The main objective of such surface modifications is to produce a strong bond through the micromechanical interlocking between fresh and old resin composites.…”
Section: Introductionmentioning
confidence: 99%